2009
DOI: 10.2967/jnumed.109.062448
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate–Binding Cassette Subfamily C Member 2 Is the Major Transporter of the Hepatobiliary Imaging Agent 99mTc-Mebrofenin

Abstract: The organic anion 99m Tc-N-[2- [(3-bromo-2,4,6-trimethylphenyl)amino]-2-oxoethyl]-N-(carboxymethyl)-glycine ( 99m Tc-mebrofenin) and its analogs are widely used for hepatobiliary imaging. Identification of the mechanisms directing bile canalicular transport of these agents will provide insights into the basis of their hepatic handling for assessing perturbations. Methods: We performed studies in animals, including healthy Fischer 344 rats or rats treated with carbon tetrachloride or intrasplenic cell transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…During the preloading phase, 99m Tc-MEB accumulates in the canalicular networks and may not be washed away completely before initiating the efflux phase; rapid canalicular excretion of 99m Tc-MEB may occur before MK571 had time to access the hepatocyte and reach the site of MRP2 inhibition, especially in human SCH. Overall, MK571 inhibition and the absence of 99m Tc-MEB in the bile canalicular networks of TR − rat SCH support the hypothesis that 99m Tc-MEB is a specific Mrp2 probe substrate, consistent with other reports documenting increased hepatic exposure of 99m Tc-MEB in TR − rats(4), and decreased biliary excretion in patients with Dubin-Johnson syndrome (MRP2-deficiency) administered 99m Tc-MEB analogs(5). 99m Tc-MEB basolateral efflux was increased in TR − rat SCH compared to WT, and in the presence of MK571 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…During the preloading phase, 99m Tc-MEB accumulates in the canalicular networks and may not be washed away completely before initiating the efflux phase; rapid canalicular excretion of 99m Tc-MEB may occur before MK571 had time to access the hepatocyte and reach the site of MRP2 inhibition, especially in human SCH. Overall, MK571 inhibition and the absence of 99m Tc-MEB in the bile canalicular networks of TR − rat SCH support the hypothesis that 99m Tc-MEB is a specific Mrp2 probe substrate, consistent with other reports documenting increased hepatic exposure of 99m Tc-MEB in TR − rats(4), and decreased biliary excretion in patients with Dubin-Johnson syndrome (MRP2-deficiency) administered 99m Tc-MEB analogs(5). 99m Tc-MEB basolateral efflux was increased in TR − rat SCH compared to WT, and in the presence of MK571 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Several hepatic transport proteins involved in the hepatobiliary disposition of 99m Tc-MEB were characterized recently in expressed systems including OATP1B1, OATP1B3, MRP2 and MRP3(3). 99m Tc-MEB exhibited increased and prolonged hepatic exposure measured by gamma scintigraphy in Mrp2-deficient TR − rats compared to WT rats, suggesting that Mrp2 is involved in canalicular transport(4). Furthermore, case reports have documented a failure to visualize the hepatobiliary tree after administration of 99m Tc-disofenin (DISIDA), the diisopropyl analogue of acetanilidoiminodiacetic acid, when administered to patients with Dubin-Johnson syndrome (MRP2-deficiency)(5).…”
Section: Introductionmentioning
confidence: 99%
“…14,18,19,20,21 Sensitivity analysis and simulations using data from the current study also confirmed that hepatic exposure was highly sensitive to biliary clearance; even modest (twofold) changes in this parameter should have an apparent effect on the slope of the liver time–activity curves. These data imply that 99m Tc–mebrofenin clearance from liver to bile in the current study was not influenced significantly by ritonavir, even though ritonavir is an MRP2 inhibitor.…”
Section: Discussionsupporting
confidence: 66%
“…13,14,15 The efficient vectorial transport of 99m Tc–mebrofenin from blood into liver is mediated by the organic anion transporting polypeptides, OATP1B1 and OATP1B3; 9,16,17 99m Tc–mebrofenin is preferentially excreted into bile unchanged by the canalicular efflux transporter multidrug resistance protein 2 (MRP2). 9,16,18 99m Tc–mebrofenin also can be excreted from hepatocytes back into blood by MRP3. 9 The important role of MRP2-mediated biliary excretion as the rate-limiting step for 99m Tc–mebrofenin elimination in vivo is evidenced by increased and prolonged hepatic exposure of 99m Tc–mebrofenin and other iminodiacetic acid analogs in preclinical species (TR − rats) and humans (Dubin–Johnson syndrome) with genetic impairment of Mrp2/MRP2.…”
mentioning
confidence: 99%
See 1 more Smart Citation